Comparison of dental surface of canine teeth in dogs after crown preparation using CBCT-based surface reconstruction or conventional dental impression materials - Metje, Benjamin; Schreyer, Jan; Lüpke, Matthias; Meller, Sebastian; Klasen, Jan R. S.; Gawor, Jerzy Pawel (Frontiers in Veterinary Science, 2025)
ObjectiveThis cadaver study evaluated accuracy of Cone Beam Computed Tomography (CBCT)-derived surface models in reproducing crown-prepared canine teeth and compared them with conventional impressions/plaster models as the current gold standard in veterinary prosthodontics.MethodsForty canine teeth underwent crown preparation. Conventional impressions with plaster model fabrication and CBCT scans at two resolutions (n = 20 0.12 mm, n = 20 0.09 mm) were obtained. Models and original teeth were digitized by precise surface scanning. Surface distance from plaster models and CBCT datasets was compared with the original teeth (reference). Mean deviations were calculated and compared statistically.ResultsPlaster models showed deviations of 9.3–56.4 μm. High-resolution CBCT scans yielded 21.3–36.4 μm; low-resolution scans 30.6–514.5 μm, with one outlier excluded. Within both cohorts, CBCT and plaster model deviations did not differ significantly; however, the two CBCT protocols differed significantly (p = 0.0058), with higher resolution producing lower deviations.ConclusionBoth CBCT protocols produced deviations comparable to plaster models in this in-vitro single-tooth setup. Higher-resolution CBCT improved accuracy, but all CBCT datasets remained within clinically acceptable ranges. CBCT may represent a feasible alternative for digital impressions in veterinary prosthodontics, though radiation exposure and clinical applicability must be considered.